The El-Amarna correspondence : a new edition of the cuneiform letters from the site of El-Amarna based on collations of all extant tablets - Rainey, Anson F., 1930-2011; Schniedewind, William M. (Handbook of Oriental Studies. Section 1 The Near and Middle East., 2014)
A new critical edition of the el-Amarna Letters based on personal examination of all the tablets.